Executive team effectiveness and organisational performance: A research program on leveraging team intellectual capital - Wood, Margot; Klass, Des; Quaddus, Mohammed (Curtin University of Technology, 2007)
This paper outlines a research program designed to develop and verify the Executive Team Effectiveness (ETE) model. The authors hypothesise that maximising the Intellectual Capital of an executive team, within any given Executive Team Domain, will result in improved Decision Quality thus impacting positively on Organisational Effectiveness.The project utilises a mixed method research design to build on published and on-going works of the principal researchers and the four phase research design includes: 1) Background Research and the Refinement of the Executive Team Effectiveness Model (Exploratory), 2) Developing the Team Intellectual Capital instrument and confirming the Team Effectiveness Domain dimensions (Explanatory), 3) Measuring Quality and developing Intervention Workshops/Training modules (Exploratory), 4) Validating the Executive Team Effectiveness Model (Explanatory).The authors argue that insights gained from their research will allow for a better understanding of the gap between a team?s potential effectiveness, represented by the TIC, and their actual performance. The authors suggest that through the application of concrete strategies in response to a TIC evaluation an Executive team?s capabilities may be developed and/or adjusted and consequently leveraged to enhance decision quality and ultimately improve organisational effectiveness.